2015
DOI: 10.1021/acs.iecr.5b00425
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced X-ray Shielding Ability of Polymer–Nonleaded Metal Composites by Multilayer Structuring

Abstract: Polymer–nonleaded metal (tungsten, Sendust) composites were prepared to study the effects of multilayer structure on X-ray shielding ability. Though the metals were nonleaded, the metal contents were low, and the composite films were thin, the composite films showed favorable X-ray shielding ability due to the uniform dispersion of metal particles in the polymer matrix and the flake alignment (Sendust). This means that multi- layered particles can effectively absorb the penetrating photons and they fill the pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 23 publications
1
37
1
Order By: Relevance
“…(Flora et al 2012;La et al 2016). The radiation attenuation property of nanomaterials has been explored extensively in the past to replace the existing toxic lead-based materials for radiation protection (Abdulla et al 2015;Adliene et al 2015;Aral et al 2016;Fujimori et al 2011;Kim et al 2015). For example, Fontainha et al (2016) have demonstrated a 60% attenuation of X-rays of energy 40 keV by the nanocomposites of poly(vinylidene fluoride-trifluoroethylene) and zirconia nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…(Flora et al 2012;La et al 2016). The radiation attenuation property of nanomaterials has been explored extensively in the past to replace the existing toxic lead-based materials for radiation protection (Abdulla et al 2015;Adliene et al 2015;Aral et al 2016;Fujimori et al 2011;Kim et al 2015). For example, Fontainha et al (2016) have demonstrated a 60% attenuation of X-rays of energy 40 keV by the nanocomposites of poly(vinylidene fluoride-trifluoroethylene) and zirconia nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Pb, the most commonly used shielding material, is therefore used because its high Z-number, high density, and low cost make it superior to other shielding materials. [7][8][9][10][11][12][13][14] Pb-based shielding materials, however, are detrimental to worker's health and also cause environmental pollution. [9,10,14] Although tungsten (W) is the most effective and promising metal substitute for Pb compounds, its specific gravity is greater than that of Pb and is difficult to use in the fabrication of protective equipment or garment because of its high melting temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[7,9] Because of the large surface-to-volume ratio of the dispersed metal particles, the composites have strong potential to absorb high-energy radiation and to be easily processed into a structured material with geometric conformability. [11][12][13] They are also lighter than their metal counterparts used in effective and durable radiation protective gear. [11] However, the metal-polymer composites have less shielding ability because of pinholes, which allow incident photons to penetrate pure polymer regions in the composite materials, and because the polymer matrix lacks shielding ability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations